Keyboards' end is just moves away. (Times Higher Education Supplement, 1996)
Focuses on the efforts of experts from City University, England to produce a computer that can recognize and act on gestures, body language and sign language to benefit the deaf and people with severe physical disabilities who want to input data. Detection of movements that correspond with computer function; Expansion of the human actions that can be used for computer input; Funding for the establishment of the computer.